2018
DOI: 10.1007/s40979-018-0030-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of tutorials for promoting educational integrity: a synthesis paper

Abstract: The prevalence of plagiarism, cheating, and other acts of academic dishonesty may be as high as 80% in populations of high school and post-secondary students. Various educational interventions have been developed and implemented in an effort to educate students about academic integrity and to prevent academic misconduct. We reviewed the peer-reviewed research literature describing face-to-face workshops, elearning tutorials, or blended approaches for promoting academic integrity and the effectiveness of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 60 publications
0
32
0
3
Order By: Relevance
“…As an immediate actor in the educational setting, the intervention strategies used by educators may focus on deterring the details of unauthorized behaviors and placing themselves as role models for younger generations. This method may be effective as focusing on the prevention of academic dishonesty has several advantages over taking remedial measures, which is stressed by (Stoesz & Yudintseva, 2018). As a result, socially responsible faculty members can help to reduce dishonesty in higher education institutions (Simkin & Mcleod, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As an immediate actor in the educational setting, the intervention strategies used by educators may focus on deterring the details of unauthorized behaviors and placing themselves as role models for younger generations. This method may be effective as focusing on the prevention of academic dishonesty has several advantages over taking remedial measures, which is stressed by (Stoesz & Yudintseva, 2018). As a result, socially responsible faculty members can help to reduce dishonesty in higher education institutions (Simkin & Mcleod, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Student involvement measured through investment, commitment and satisfaction in the honour code significantly predicted the outcome of upholding of the honour code (Dix et al 2014). Based on a review, tutorials inclusive of face to face and e-learning sessions were associated with improvements in knowledge and skill related to academic integrity (Stoesz and Yudintseva 2018). These authors further concluded that inclusion of hands-on training within these teaching sessions resulted in longer term benefits for the students.…”
Section: Strategy For the Honour Codementioning
confidence: 94%
“…For example, results from field-based quasi-experimental ( Belter and du Pré, 2009 ) and experimental ( Dee and Jacob, 2010 ) research showed that completion of online tutorials related to plagiarism greatly reduced its occurrence – by 75.4% in the former study and an estimated 41% in the latter. However, as noted in the introduction, there is no evidence to date that the effects of these tutorials extend beyond the immediate context (i.e., the academic course) in which they are implemented ( Stoesz and Yudintseva, 2018 ). Additionally, the empirical research on the effects of academic integrity instruction has yet to include any delayed testing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The past decade, in particular, has seen an increase in efforts among universities to promote academic integrity among students. These efforts include face-to-face workshops and online courses as well as blended learning approaches ( Stoesz and Yudintseva, 2018 ). The most common (and growing) approach appears to be requiring (or at least encouraging) incoming students to complete a short, web-based course or tutorial on academic integrity.…”
Section: Introductionmentioning
confidence: 99%